Wheat Blast —A menace to wheat cultivation - Ray, Krishna; Borah, Tasvina R; Pahil, Virender Singh; Rana, M K (Indian Farming, 2022)
The wheat blast fungi, Magnaporthe oryzae pathotype triticum, has more than 50 hosts to complete its life cycle. This disease was first reported from South America, Brazil. Sudden outbreak of this disease was reported in 2016 in Bangladesh. The states of Bangladesh near the border of West Bengal are at risk for cultivating wheat. This can be the cue for this pathogen to take entry into India. Therefore, care should be taken by implementing regular monitoring and continuous vigilance to prevent the entry of the pathogen in India.